Diversity of Reproductive Phenology Among Subtropical Grasses Is Constrained by Evolution and Climatic Niche - Li, Kangxin; Wang, Jinying; Qiao, Lu; Zheng, Ruyi; Ma, Yiqun; Chen, Yuan; Hou, Xiaobo; Du, Yanjun; Gao, Jianguo; Liu, Hui (Frontiers in Ecology and Evolution, 2020)
Reproductive phenology is sensitive to climatic changes, and is associated with species functional types, distribution ranges and their corresponding climatic niches. Phylogenetic niche conservatism in reproductive phenology also constrains its diversity and distribution of species. Therefore, we assessed the effects of photosynthetic pathway, life history, phylogeny and climatic niche on reproductive phenology. For 190 Poaceae species in subtropical China, we compiled data on flowering onset and reproductive period, functional type (photosynthetic pathway and life history) and 18 climatic variables across species’ global distributions, and used phylogenetic models to determine associations. We found strong phylogenetic signals in flowering onset but not reproductive period. Photosynthetic pathway and life history have significant interactive effects on both flowering onset and reproductive period, such that C3-annual grasses flowered the earliest, and had the longest reproductive period. Similarly, we found that species with wider climatic niches would flower earlier and have longer reproductive periods. Specifically, species that experience wider ranges of mean annual precipitation and coldest-month temperatures would flower earlier, and species with higher mean annual temperature and wider ranges of wettest-quarter precipitation have longer reproductive period. This study finds that the diversity of reproductive phenology among subtropical grasses is constrained by evolution and climatic niche, and that photosynthetic pathway and life history have an interactive effect on the timing and duration of reproduction.